Gambaran Tingkat Pengetahuan Ibu Nifas Tentang Diet Saat Menyusui di RS PKU Muhammadiyah Bantul Yogyakarta - Elvika Fit Ari Shanti; Chindy Puspita Dewi (Journal of Health (JoH), 2017)
Background of Study: During lactation, women will have optimal weight gain, it causes mothers reduce their food so that interfere breast-milk production. Diet during breastfeeding may be done, but it must be done slowly. It is necessary to defend the body against infections, to prevent constipation and to begin the process of exclusive breastfeeding. Knowledge of this diet is very important for postpartum mothers who want to go on a diet to avoid malnutrition during childbirth and lactation. Preliminary results of study showed that it appeared in PKU Muhammadiyah Hospital in Bantul there are many postpartum mothers who do not know about the importance of diet during breastfeeding. Objective of Study: This study aims to know about the level of knowledge of postpartum women about diet during breastfeeding in July 2014 at PKU Muhammadiyah Hospital in Bantul, Yogyakarta. Research Methods: This study uses quantitative descriptive method, with survey approach. The population in this study is 58 postpartum women. To collect the data, this study uses accidental sampling technique. The samples taken amounted to 35 for women. The research data is primary data by using the research instrument in the form of a questionnaire and data analysis using univariate analysis Results: The level of knowledge about understanding of diet postpartum women in both categories as many as 16 people (45.7%), on the definition of a balanced diet as many as 31 people (88.6%), on the correct diet while breast-feeding as many as 20 people (57.1 %), on dietary goals in less category as much as 23 people (65.7%), on the principle of the diet as much as 22 people (62.9%), on the terms of diet in both categories as many as 14 people (40.0%), about the benefits diet in less category as much as 22 people (62.9%). Conclusion: The results of the level of knowledge of puerperal women while breastfeeding diet in PKU Muhammadiyah Hospital are in quite as many as 20 categories of puerperal women (57.1%).